The AFCFTA protocol on investment as a catalyst to promote sustainable development in Cameroon - Ngobeni, Tinyiko (University of Pretoria, 2025)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2025.